Outcomes of adrenal-sparing surgery or total adrenalectomy in phaeochromocytoma associated with multiple endocrine neoplasia type 2: an international retrospective population-based study - (:unkn) unknown (ELSEVIER SCIENCE INC, 2014)
Background The prevention of medullary thyroid cancer in patients with multiple endocrine neoplasia type 2 syndrome has demonstrated the ability of molecular diagnosis and prophylactic surgery to improve patient outcomes. However, the other major neoplasia associated with multiple endocrine neoplasia type 2, phaeochromocytoma, is not as well characterised in terms of occurrence and treatment outcomes. In this study, we aimed to systematically characterise the outcomes of management of phaeochromocytoma associated with multiple endocrine neoplasia type 2. Methods This multinational observational retrospective population-based study compiled data on patients with multiple endocrine neoplasia type 2 from 30 academic medical centres across Europe, the Americas, and Asia. Patients were included if they were carriers of germline pathogenic mutations of the RET gene, or were first-degree relatives with histologically proven medullary thyroid cancer and phaeochromocytoma. We gathered clinical information about patients' RET genotype, type of treatment for phaeochromocytoma (ie, unilateral or bilateral operations as adrenalectomy or adrenal-sparing surgery, and as open or endoscopic operations), and postoperative outcomes (adrenal function, malignancy, and death). The type of surgery was decided by each investigator and the timing of surgery was patient driven. The primary aim of our analysis was to compare disease-free survival after either adrenal-sparing surgery or adrenalectomy. Findings 1210 patients with multiple endocrine neoplasia type 2 were included in our database, 563 of whom had phaeochromocytoma. Treatment was adrenalectomy in 438 (79%) of 552 operated patients, and adrenal-sparing surgery in 114 (21%). Phaeochromocytoma recurrence occurred in four (3%) of 153 of the operated glands after adrenal-sparing surgery after 6-13 years, compared with 11 (2%) of 717 glands operated by adrenalectomy (p=0.57). Postoperative adrenal insufficiency or steroid dependency developed in 292 (86%) of 339 patients with bilateral phaeochromocytoma who underwent surgery. However, 47 (57%) of 82 patients with bilateral phaeochromocytoma who underwent adrenal-sparing surgery did not become steroid dependent. Interpretation The treatment of multiple endocrine neoplasia type 2-related phaeochromocytoma continues to rely on adrenalectomies with their associated Addisonian-like complications and consequent lifelong dependency on steroids. Adrenal-sparing surgery, a highly successful treatment option in experienced centres, should be the surgical approach of choice to reduce these complications.
Keywords: MEDULLARY-THYROID CARCINOMA; RET PROTOONCOGENE; GERMLINE MUTATIONS; DISEASE; 2A; MANAGEMENT